Pengaruh Penekanan Terhadap Kadar Air, Kadar Abu, Dan Nilai Kalor Briket Dari Sludge Biogas Kotoran Sapi - Zeni Ulma; Murni Handayani; Arsita Nur Rizkia Putri; Choirunnisa Firdaus Ivana (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2021)
Utilization of biogas sludge waste from cow dung into briquettes is an alternative to reduce the use of fossil fuels. In the manufacture of briquettes made from biogas sludge, molasses is used as an adhesive which is a by-product of a sugar factory. In this study, variable compression briquettes with variations of 10, 15, 20, and 25 mm were used and further testing was carried out on the moisture content, ash content, and calorific value of the briquettes. The effect of briquette compression on the water content of the best briquettes according to the SNI standard (less than 8%) is at 10 mm compression variation with a moisture content value of 6.03%. Meanwhile, the effect of pressing briquettes on the ash content and calorific value is still above the SNI standard and requires further study.